Deoxyribonucleic Acid Base Composition of the Yeastlike and Mycelial Phases of Histoplasma capsulatum and Blastomyces dermatitidis - Bawdon, Roger E. (1972)
The base composition in moles percent guanine plus cytosine (%GC) of both nuclear and mitochondrial deoxyribonucleic acid (DNA) isolated from the yeastlike and mycelial phases of the dimorphic fungal pathogens Histoplasma capsulatum and Blastomyces dermatitidis was determined by techniques of thermal denaturation and CsCl buoyant density gradient equilibrium centrifugation. The mean observed values for GC content of nuclear DNA from H. capsulatum and B. dermatitidis were 47.3 and 48.2%, respectively. What is speculated to be mitochondrial DNA was found to be 34.0% for H. capsulatum and 34.3% for B. dermatitidis. Thermal denaturation curves for Blastomyces DNA indicated a bimodality in thermal denaturation profiles, thereby suggesting a significant mitochondrial DNA contamination. Mitochondrial DNA appeared to represent a smaller percentage of the total DNA prepared from Histoplasma, and was not observed consistently to affect%GC values as determined by thermal denaturation profiles. On the basis of the now known perfect stage of B. dermatitidis (Ajellomyces dermatitidis) as a member of the family Gymnoascaceae, the close approximation of%GC content of nuclear DNA of this fungal organism with that of H. capsulatum suggests possible phylogenetic relationship. It is suggested that the just reported, but as yet unclassified, perfect stage of H. capsulatum may be found to be phylogenetically a primitive form of the Gymnoascaceae.